2020
DOI: 10.1167/jov.20.7.19
|View full text |Cite
|
Sign up to set email alerts
|

Trans-saccadic adaptation of perceived size independent of saccadic adaptation

Abstract: Systematic shortening or lengthening of target objects during saccades modifies saccade amplitudes and perceived size of the objects. These two events are concomitant when size change during the saccade occurs asymmetrically, thereby shifting the center of mass of the object. In the present study, we asked whether or not the two are necessarily linked. We tested human participants in symmetrical systematic shortening and lengthening of a vertical bar during a horizontal saccade, aiming to not modify the saccad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…This absence of significant variation of size perception may suggest that perceptual size responses, after a grasping movement, are not affected equally in both directions of horizontal perturbation. Bosco et al (2020) reported similar findings [ 46 ]. While in our study the horizontal bar size was modified during the origin of the grasping movement, in their experiment, size perturbation was based on the onset of the saccadic eye movements [ 46 ].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This absence of significant variation of size perception may suggest that perceptual size responses, after a grasping movement, are not affected equally in both directions of horizontal perturbation. Bosco et al (2020) reported similar findings [ 46 ]. While in our study the horizontal bar size was modified during the origin of the grasping movement, in their experiment, size perturbation was based on the onset of the saccadic eye movements [ 46 ].…”
Section: Discussionsupporting
confidence: 55%
“…Nevertheless, we found a modification of saccade amplitude following horizontal size perturbation during grasping movement execution. As observed in size perceptual responses, the reported impact was not strictly bidirectional, suggesting different mechanisms in the oculomotor system for different size perturbation conditions [ 46 , 51 , 52 ]. Several studies have investigated the plasticity of the saccadic system; observing how changes in object size during saccadic execution generate changes in amplitude, consistent with the direction in size change [ 33 , 38 , 46 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Saccade adaptation has been shown to alter the geometric properties of the perceptual visual field, which in turn can modify the perceived shape of objects ( Garaas & Pomplun, 2011 ), and there is very recent evidence that saccade adaptation per se can modify the perceived size of peripheral stimuli ( Pressigout, Paeye, & Doré-Mazars, 2020 ). 4 Moreover, when saccade adaptation and perceptual re-calibration are established within the same paradigm, their strength tends to correlate across observers ( Bosco et al, 2015 ), although transsaccadic re-calibration of perceived size can be established in the absence of saccade adaptation if the expansion or contraction of the target stimulus is orthogonal to the saccade vector ( Bosco, Rifai, Wahl, Fattori, & Lappe, 2020 ). Specifically, Valsecchi and colleagues (2020 ) investigated the temporal and spatial properties of transsaccadic size re-calibration.…”
Section: Re-calibration Of Peripheral and Foveal Visionmentioning
confidence: 99%
“…Peripheral vision and foveal vision differ in many ways, so in order for a prediction to be useful (depending on the feature involved) the brain must take into account the relative reliability of the two sources of information (preview and post-saccadic foveal view) in order to optimally use the preview information (Ganmor, Landy, & Simoncelli, 2015;Stewart & Schütz, 2018;Wolf & Schütz, 2015). On the other hand, saccadic contingencies, in the sense of predictable changes in a stimulus across the saccade, even lead to a re-calibration of the perceptual appearance of the extrafoveal preview (Bompas & O'Regan, 2006;Bosco, Lappe, & Fattori, 2015;Bosco, Rifai, Wahl, Fattori, & Lappe, 2020;Herwig & Schneider, 2014;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020;Valsecchi & Gegenfurtner, 2016; for a review see Stewart et al, 2020) which suggests that "what" predictions across a saccade can be relatively specific. Whether the preview effect can also be related to predicting the "when" and "where" of post-saccadic stimulation is yet to be explored.…”
Section: An Active-vision Interpretation Of Preview Effectsmentioning
confidence: 99%